1991
DOI: 10.1104/pp.95.4.1229
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the System Regulating Proton Movement across the Chloroplast Envelope

Abstract: Studies were undertaken to further characterize the spinach (Spinacea oleracea) chloroplast envelope system, which facilitates H+ movement into and out of the stroma, and, hence, modulates photosynthetic activity by regulating stromal pH. It was demonstrated that high envelope-bound Mg2+ causes stromal acidification and photosynthetic inhibition. High envelope-bound Mg2+ was also found to necessitate the activity of a digitoxinand oligomycin-sensitive ATPase for the maintenance of high stromal pH and photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…One clear effect of Mg2" binding to the envelope is an inhibition of K+ uptake. However, the data reported here support the results of previous studies (2,11,14,18) in that Mg2e inhibition of photosynthesis was demonstrated to be caused directly by stromal acidification. The data suggest that Mg2+-induced stromal acidification is not due to the action of a Mg2+-activated K+/H+ antiporter or to changes in the ionic strength of the bulk solution external to the chloroplast but possibly due to the metal ion's effects on the current through monovalent cation channels in the envelope.…”
Section: Mg2' Treatmentssupporting
confidence: 74%
See 1 more Smart Citation
“…One clear effect of Mg2" binding to the envelope is an inhibition of K+ uptake. However, the data reported here support the results of previous studies (2,11,14,18) in that Mg2e inhibition of photosynthesis was demonstrated to be caused directly by stromal acidification. The data suggest that Mg2+-induced stromal acidification is not due to the action of a Mg2+-activated K+/H+ antiporter or to changes in the ionic strength of the bulk solution external to the chloroplast but possibly due to the metal ion's effects on the current through monovalent cation channels in the envelope.…”
Section: Mg2' Treatmentssupporting
confidence: 74%
“…This hypothesis seemed plausible in light of our recent work in which we postulated the presence of K+ channels in chloroplast envelopes (18).…”
Section: Mg2' Treatmentsmentioning
confidence: 96%
“…Earlier biochemical and physiological data suggested that an unknown Na ϩ (K ϩ )͞H ϩ antiporter is localized in the chloroplast envelope, partially regulating stromal acidification and alkalization (7,8,30). The stroma pH level is an important factor for high photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Electroneutral monovalent cation͞proton antiport across the chloroplast envelope was shown to have a strong effect on the chloroplast stroma pH and could thereby either help or inhibit photosynthesis (6,7). Subsequent work (8,9) indicated the existence of a complex regulatory system, including a monovalent cation͞proton antiporter, monovalent cation channels, and ATPase-dependent H ϩ efflux, across the chloroplast envelope. However, none of the hypothesized chloroplast envelope transporters have been identified as yet.…”
mentioning
confidence: 99%
“…Inhibitor studies with intact isolated chloroplasts further suggest that trans-envelope K+ flux may occur through a putative ion channel (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%